Incorporation of barium titanate nanoparticles in piezoelectric PVDF membrane - Su, Yu Ping (2021)
The micro-vibration of piezoelectric polyvinylidene fluoride (PVDF) membranes has been shown to mitigate fouling. To improve the desired piezoelectric properties, piezoelectric barium titanate (BaTiO3) nanoparticles (NPs) were incorporated into PVDF membranes fabricated by non-solvent induced phase separation (NIPS). Due to the high surface energy of BaTiO3 NPs, the nanoparticles tended to agglomerate and were not dispersed uniformly. The silane coupling agent (3-Aminopropyl)triethoxysilane (APTES) with the BaTiO3 NPs showed enhanced compatibility and dispersion in the PVDF membrane. The resulting BaTiO3-PVDF membranes had similar finger-like pore structure as neat PVDF membrane. The dielectric strength, piezoelectric and mechanical properties of BaTiO3-PVDF membranes were enhanced. A linear correlation (R2 = 0.9391) between piezoelectric coefficient and critical flux was observed for poled BaTiO3-PVDF membranes under the influence of electrical AC signal (10 Vpp, 500 Hz) when colloidal silica was used as model foulant. The optimal BaTiO3-PVDF membrane (0.1 wt% BaTiO3, poled and AC applied) showed up to 51% increase in critical flux compared to the neat PVDF membrane (unpoled and no AC applied). Further, extended durations of multiple filtration cycles by up to a factor of 2 to 4 were observed. The membrane operation could be prolonged due to significant reduction in irreversible fouling.